Correction: Ultra-efficient and stable electro-optic dendrimers containing supramolecular homodimers of semifluorinated dipolar aromatics. (5th March 2018) - Wu, Jieyun; Wu, Bo; Wang, Wen; Chiang, Kin Seng; Jen, Alex. K.-Y.; Luo, Jingdong
Abstract : Correction for 'Ultra-efficient and stable electro-optic dendrimers containing supramolecular homodimers of semifluorinated dipolar aromatics' by Jieyun Wu et al., Mater. Chem. Front., 2018, DOI: ;10.1039/c8qm00006a .